The Fund's Lending Framework and Sovereign Debt : Preliminary Considerations. (Policy Papers; Policy Paper ;, 2014)
As a follow-up to theaExecutive Board's May 2013 discussion, this paper considers a possible direction for reform of the Fund's lending framework in the context of sovereign debt vulnerabilities. The primary focus of this paper relates to the Fund's exceptional access framework, since it is in this context that the Fund will most likely have to make the difficult judgment as to whether the member's problems can be resolved with or without a debt restructuring. The objective of the preliminary approaches set forth in this paper is to reduce the costs of crisis resolution for both creditors and debtors-relative to the alternatives-thereby benefitting the overall system. These ideas are market-based and their eventual implementation would require meaningful consultation with creditors.